THE APPLICATION OF CYCLOSTRATIGRAPHY AND ASTROCHRONOLOGY IN THE NEOGENE MARINE DEPOSITS OF EASTERN MEDITERRANEAN: METOCHIA SECTION (GAVDOS ISLAND) - Antonarakou, A.; Drinia, H.; Pomoni-Papaioannou, F. (Bulletin of the Geological Society of Greece, 2006)
Significant lithostratigraphical and micropaleontological signatures, of Milankovitchscale climatic changes are recorded in Miocene deep-sea sediments. As a case study, the Metochia Section, in Gavdos Island, which covers the time interval from 9.7 to 6.6 Ma, is used. This study emphasizes the sedimentological and micropaleontological characteristics of the section, attributed to Milankovitch-scale climatic changes. The short-term variations in climate and faunal composition are related to precession- controlled sedimentary cycles and the long-term trend in climate is related to eccentricity and obliquity cycles. Regional changes in sea surface temperature in combination with variations of solar insolation have caused the cyclical astronomical controlled pattern of Globorotalia species.